TRANSPARENCY INCREASEMENT OF OPEN GOVERNMENT DATA: PERCEPTION OF BRAZILIAN CITIZEN OBSERVATORIES - Hickmann Klein, Rodrigo; Barbiero Klein, Deisy Cristina; Mezzomo Luciano, Edimara (Contextus - Revista Contemporânea de Economia e Gestão, 2019)
Open Government Data (OGD) promote transparency by making government data public and allowing the accountability of public officials and elected representatives for their actions and decisions. The purposes of this research are to identify and to evaluate the importance of mechanisms that can increase OGD transparency and thus meet the purpose of accountability processes. Such mechanisms were identified through a systematic literature review and validated by the participation of OGD experts and 92 OGD users represented by members of so-called Social Observatories. All mechanisms were considered at least important by most respondents. The importance attributed to the mechanisms emphasizes the quality and reliability required for the reuse of OGD. The results obtained are relevant to the practice of public managers who wish to evaluate the transparency of OGD publications and formulate strategies and public policies to disseminate them.